2015
DOI: 10.7235/hort.2015.14192
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Activities Using Colorful Food for the Improvement of Emotional Intelligence and the Reduction of Unbalanced Vegetable Diet of Young Children

Abstract: This study focuses on horticultural activities using colorful food to reduce diets unbalanced in vegetables and to increase emotional intelligence. Horticultural activities using colorful food vegetables were based on ʻHealth in Daily Lifeʼ in the ʻ7th Kindergarten Curriculumʼ; to improve the dietary habits of the young children, the program was also linked with a parentsʼ education program. The research was conducted with a total of 70 children from classes for four-year-olds in three child-care centers locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, compared to preschoolers who participated in taking a walk, those who participated in horticultural activities based on direct experience of nature showed improvement in emotional intelligence as well as sub-factors such as emotional self-awareness, emotional self-regulation, emotional awareness of others, and emotional regulation of others(Ryu et al, 2013). Moreover, in consistent with the study proving that horticultural activities in which participants could actually cultivate color food vegetables helped them consume vegetables voluntarily, thereby significantly reducing avoidance of vegetables and improving emotional intelligence(Son et al, 2015), it is reported that active participation in horticultural activities resulted in greater effect than passive and participation in horticultural activities. Furthermore, preschool children that participated in horticultural activities accepted them as fun and interesting, and preferred plant activities in which they had participated and have much experience(Park and Huh, 2010).As a result of a meta-analysis on the effects of horticultural activities and horticultural therapy in each class, it was found that implementing 11 sessions of the horticultural program is more effective than implementing 10 or less…”
supporting
confidence: 81%
“…However, compared to preschoolers who participated in taking a walk, those who participated in horticultural activities based on direct experience of nature showed improvement in emotional intelligence as well as sub-factors such as emotional self-awareness, emotional self-regulation, emotional awareness of others, and emotional regulation of others(Ryu et al, 2013). Moreover, in consistent with the study proving that horticultural activities in which participants could actually cultivate color food vegetables helped them consume vegetables voluntarily, thereby significantly reducing avoidance of vegetables and improving emotional intelligence(Son et al, 2015), it is reported that active participation in horticultural activities resulted in greater effect than passive and participation in horticultural activities. Furthermore, preschool children that participated in horticultural activities accepted them as fun and interesting, and preferred plant activities in which they had participated and have much experience(Park and Huh, 2010).As a result of a meta-analysis on the effects of horticultural activities and horticultural therapy in each class, it was found that implementing 11 sessions of the horticultural program is more effective than implementing 10 or less…”
supporting
confidence: 81%
“…The population-based study [ 11 ] only had a cross-sectional measurement of emotional and behavioral outcomes and did not assess fruit and vegetable intakes. In addition, previous studies on the relationship between eating habits and behavior outcomes of preschoolers reported that preschoolers who hated vegetables exhibited high self-centeredness, aggressiveness, and high anxiety [ 18 ], whereas preschoolers with poor eating habits showed lower adaptability, stability, sociability, and higher self-esteem than those with good eating habits, although a direct comparison was not feasible due to a lack of measurement of fruit and vegetable intakes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As per the search results, 40 research papers were used as reference to verify the effectiveness of the garden-based program to improve children's eating behavior. The five factors that mediated the association between garden-based activity and children's eating behavior for vegetables and fruits extracted from 40 studies were "skills required to engage in gardening" [23][24][25], "knowledge of nutrition, fruit, and vegetable" [19,[26][27][28], "willingness to try new food (food neophobia)" [25,26,29], "dietary self-efficacy" [19,27,28], and "fruit and vegetable preference" [19,[25][26][27][28][29].…”
Section: Program Developmentmentioning
confidence: 99%
“…Accordingly, various methods such as school garden programs, nutrition education, or cooking activities have been attempted to improve children's eating behavior worldwide [11][12][13]. In particular, gardening, in which children themselves plant, grow, and harvest vegetables, have been reported to reduce their revulsion toward vegetables and increase their preference for and understanding of various types of foods and leading to increased vegetable consumption [14][15][16][17][18][19]. In a previous study, as 304 students predominately Hispanic/Latino third-through fifth-grade in elementary school were randomly assigned to either the LA Sprouts group (nutrition, cooking, and gardening intervention) or control group, a number of determinants of dietary behaviors such as identification of vegetables and nutrition and gardening knowledge for LA Sprouts group has positively changed after the program [20].…”
Section: Introductionmentioning
confidence: 99%